Short-Term Bisphosphonate Therapy Could Ameliorate Osteonecrosis: A Complication in Childhood Hematologic Malignancies. (30th May 2010) - Greggio, N. A.; Pillon, M.; Varotto, E.; Zanin, A.; Talenti, E.; Palozzo, A. C.; Calore, E.; Messina, C.
Abstract : Osteonecrosis (ON) is a critical complication in the treatment of childhood leukemia and lymphoma. It particularly affects survivors of acute lymphoblastic leukemia and non-Hodgkin lymphoma reflecting the cumulative exposure to glucocorticosteroid therapy. ON is often multiarticular and bilateral, specially affecting weight-bearing joints. A conventional approach suggests a surgical intervention even if pharmacological options have also recently been investigated. We reported two cases of long time steroid-treated patients who underwent Bone Marrow Transplantation (BMT) for hematological disease. Both patients developed femoral head osteonecrosis (ON) that was diagnosed by magnetic resonance imaging (MRI) and the ON was also accompanied with pain and a limp. Despite of the conventional strategies of therapy, we successfully started a short-term treatment with bisphosphonates in order to decrease the pain and the risk of fracture.